Criminalization of Money Politics in the 2009 General Election for Candidates for Members of the Regional People's Representative Council (DPRD) of Semarang City: Pemidanaan Money Politic dalam Penyelenggaraan Pemilihan Umum Calon Anggota DPRD Kota Semarang Tahun 2009 - Yudhistira Zia Ersyada (Universitas Negeri Semarang, 2012)
Indonesia as a democratic state of law, and elections are a must, as a command contained in the Act of 1945. As a democratic country, then the election should be conducted in accordance with the rules set and the violation of the rule of law must be dealt with and prosecuted by law. Organized based on the principle of direct elections, general, free, confidential, honest and fair. This study aims to determine and understand the reality of money politics a criminal act that occurred in the implementation of the General Election Candidates for the Regional Representatives Council of the city of Semarang in 2009: later to find out and analyze the handling or enforcement of any criminal violation of money politics Election Candidates for City Legislature Semarang in 2009. The data used are primary and secondary data. Analytical approach used is to approach cases and legislation. These results indicate that both the election offense of criminal or administrative, is quite difficult to enforce because of the elect